PERAN KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI MTS NEGERI SAMBOJA KABUPATEN KUTAI KARTANEGARA - Nasuha . (Jurnal Paradigma (JP), 2017)
The role of leadership in enhancing the teacher’s performance in MTsN Samboja Kutai Kartanegara is good. The many indicators to consider head’s role as manager; development of short term program, both academic or non-academic; mastering the materials of teaching; capability in managing the class; assessment and evaluation the strategy and teaching method.